The Impact of Race, Education, Economic Vulnerability, and Stigma on Viral Load Detectability Among People Living with HIV in Brazil - Brandelli Costa A; Graeff Bins-Ely I; Penzato V; Vaitses Fontanari AM; Alckmin-Carvalho F; Pereira H; Welter Wendt G (HIV/AIDS: Research and Palliative Care, 2025)
Angelo Brandelli Costa,1,2 Isadora Graeff Bins-Ely,1 Valentina Penzato,2 Anna Martha Vaitses Fontanari,3 Felipe Alckmin-Carvalho,4 Henrique Pereira,4 Guilherme Welter Wendt5 1Graduate Program in Psychology, Pontifical Catholic University of Rio Grande do Sul, Porto Alegre, Rio Grande do Sul, Brazil; 2Department of Psychological and Social Sciences, John Cabot University, Rome, Italy; 3Graduate Program in Medicine, Pontifical Catholic University of Rio Grande do Sul, Porto Alegre, Rio Grande do Sul, Brazil; 4Department of Psychology and Education, University Beira Interior, Covilhã, Portugal; 5Graduate Program in Applied Health Sciences, Western Paraná State University, Francisco Beltrão, Paraná, BrazilCorrespondence: Angelo Brandelli Costa, Pontifical Catholic University of Rio Grande do Sul, Av. Ipiranga, 6681. Prédio 11, 9º andar, Porto Alegre, Rio Grande do Sul, CEP 90619-900, Brazil, Email angelo.costa@pucrs.brBackground: Understanding barriers to viral undetectability is crucial for developing targeted interventions for populations struggling with treatment adherence. The aim of this study was to investigate the impact of race, education, economic vulnerability and HIV-related stigma on viral load detectability among people living with HIV (PLWHA) in Brazil.Methods: This was a cross-sectional, community-based study. The sample consisted of 1767 participants. We used the Brazilian version of the HIV Stigma Index 2.0 questionnaire, the Internalized AIDS-Related Stigma Scale, and a sociodemographic questionnaire. Viral load was self-reported. Data were collected by 30 PLHV themselves in 2019, after receiving training on the Brazilian Stigma Index. Data was analyzed with both descriptive and inferential statistics using SPSS.Results: Our generalized linear model showed that participants who were non-white, with low education and of lower economic status had a lower likelihood of reporting undetectable viral load (UVL) compared compared to their respective counterparts (white participants, those with higher education, and those of higher economic status). Key population group membership was not significantly associated with UVL. Higher internalized stigma was negatively associated with lower UVL.Conclusion: Our findings highlight the impact of racial, educational and economic disparities and internalized stigma on HIV outcomes and underscore the need for tailored interventions that address the specific challenges faced by different racial/ethnic and more vulnerable groups. These findings challenge the dominant treatment-as-prevention framework that focuses primarily on key populations, suggesting the need to broaden our focus to include other vulnerable populations, such as non-whites and those experiencing economic hardship. Such approach is critical to avoid overlooking situations where community viral load remains high.Keywords: HIV-related stigma, HIV/AIDS, key populations, HIV/AIDS prevention, HIV/AIDS treatment, viral load